2003
DOI: 10.1152/jn.00016.2002
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Changes in Motor Cortex Cell Activity With Arm Posture During Directional Isometric Force Generation

Abstract: . Systematic changes in motor cortex cell activity with arm posture during directional isometric force generation. J Neurophysiol 89: 212-228, 2003. 10.1152/jn.00016.2002. We report here the activity of 96 cells in primate primary motor cortex (MI) during exertion of isometric forces at the hand in constant spatial directions, while the hand was at five to nine different spatial locations on a plane. The discharge of nearly all cells varied significantly with both hand location and the direction of isometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 67 publications
7
89
0
Order By: Relevance
“…The shifts appeared consistent when the arm was rotated around an axis that was perpendicular to the work plane (Caminiti et al, 1991;Sergio and Kalaska, 2003;Morrow et al, 2007). However, the use of a larger rotation of the hand (180°) enabled dissociation between the external, muscle, and hand-orientation representations that was difficult to obtain in previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The shifts appeared consistent when the arm was rotated around an axis that was perpendicular to the work plane (Caminiti et al, 1991;Sergio and Kalaska, 2003;Morrow et al, 2007). However, the use of a larger rotation of the hand (180°) enabled dissociation between the external, muscle, and hand-orientation representations that was difficult to obtain in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…A dynamic index (DI) was computed to quantify posture-related changes in the level of force-direction firing of single-cells (Sergio and Kalaska, 2003): DI ϭ (DRp Ϫ DRs)/(DRp ϩ DRs). DRp and DRs were defined as the difference between the maximal versus minimal targetrelated firing in pronation and supination, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…22 Cortical neurons discharge at different rates depending on the direction, acceleration, and force of movement into space for reaching or stepping. 23 With new demands and training, these neurons can represent different movements. Sensory feedback, such as proprioception, has a crucial effect on motor ability at cortical and spinal levels as it reshapes sensorimotor integration.…”
Section: Neuroscientific Bases For Rehabilitationmentioning
confidence: 99%
“…In particular, the direction of end effector movement is represented using population codes [1,2] defined over neurons tuned to particular preferred directions (see next section for details). In contrast, the lower level system comprising the motor cortex (M1), the spinal cord (SC) and intermediate systems represents posture-dependent muscle force signals needed to execute the actions [16,17,20]. Thus, with reference to sequential actions, the overall system implements a convenient division of labor, where motor sequences such as writing letters or words, drawing shapes, playing key sequences, etc., are learned as action programs at an abstract, posture-and effector-independent kinematic level in the PFC/PM/SMA system, and are then "translated" into sequences of motor commands by M1 [3], possibly guided by the basal ganglia and cerebellum [23,30,31].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Experiments with primates have shown that complex voluntary movements are encoded at multiple levels in the cortex, brainstem and the spinal cord [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, the overall process by which such movements are generated remains a subject of significant debate [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%